Inflammasomes and IL-1 family cytokines in SARS-CoV-2 infection: from prognostic marker to therapeutic agent. (September 2022) - Declercq, Jozefien; De Leeuw, Elisabeth; Lambrecht, Bart N.
Abstract: Despite global vaccination programs, infections with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) continue to cause severe disease with significant morbidity and mortality. Severe coronavirus disease 2019 (COVID-19) is characterized by an exuberant inflammatory response in the lung leading to acute lung injury and consequent gas exchange problems. Complete insights in this hyperinflammatory response are still lacking. However, a thorough understanding of immunopathogenesis of severe COVID-19 is needed to not only develop personalized targeted therapies, but also to identify biomarkers that predict disease outcome and therapeutic responses. Here we review the current evidence that SARS-CoV-2 activates the inflammasome, which is an intracellular multiprotein complex that leads to the activation and secretion of the interleukin (IL)-1 family cytokines, IL-1β and IL-18, and to a lytic form of cell death, called pyroptosis. Further we discuss the contribution of inflammasomes and IL-1 family cytokines to the immunopathogenesis of COVID-19 and its clinical implications.